Organo-mineral Fertilizer Containing Struvite from Liquid Digestate for Cucurbita pepo L. Seedling Production - Melito, Sara; Ronga, Domenico; Marceddu, Daniele; Kallikazarou, Nomiki; Antoniou, Maria G.; Giannini, Vittoria (My University, 2023)
The increasing demand for sustainable fertilizers has made phosphorus recovery from waste a win–win solution. The present study shows the effects of two different types of organo-mineral fertilizers, derived from liquid digestate, on Cucurbita pepo L. (zucchini) seed germination and seedling growth. Organo-mineral fertilizers (OMF) were obtained from two biogas plants—one in Cyprus and one in Sardinia. In Cyprus, it was extracted from the digestate of mixed agricultural by-products. In Sardinia, it was extracted from the digestate of bovine slurry. Different treatment levels, compared with the traditional fertilizers, were applied in a nursery: (i) business-as-usual (0.04 g of N, 0.03 g of P2O5, 0.07 of K2O per seedling), (ii) half business-as-usual level, (iii) double business-as-usual level. Agronomic, physiological, and quality parameters were assessed. At the germination level, comparable results were shown for traditional fertilizers and OMF treatments. A significant rate-response effect was observed for leaf number and area. Cyprus OMF and traditional fertilizer showed a comparable trend with the highest value at the double business-as-usual level or fertilizer. A similar trend was observed for other biometric parameters and for fresh and dry biomasses. The highest total polyphenol and anthocyanin values were recorded under Cyprus OMF and traditional fertilizer treatments at the business-as-usual level. Cyprus OMF at the highest level (2BAU, business-as-usual) presents a comparable effect on seedling growth and to traditional fertilizers probably due to the use of different agro-industrial by-products and suggesting its potential use as an alternative nutrient supply.
Keywords: Cucurbita pepo L; Fertilizer; Germination; Morphological Response; Seedling Growth; Struvite